Pelayanan Terhadap Kepuasan Masyarakat pada RPTRA di Wilayah Jakarta Pada Masa Pandemi Covid-19 - Agung Edi Rustanto (Kolaborasi : Jurnal Administrasi Publik, 2021)
Green open space in Jakarta is very minimal due to the large number of construction of office buildings, shopping centers and others. The DKI Jakarta Provincial Government has a solution to the problem of the lack of green open space by building a Child Friendly Integrated Public Space (RPTRA). Basically the RPTRA in Jakarta is very well received by the community. The RPTRA is optimally utilized by the community to carry out various activities. Basically, community satisfaction is very high with the program, but currently community satisfaction has decreased due to the COVID-19 pandemic. The problems faced during the COVID-19 pandemic are the lack of management ability to provide services online and the absence of a special program from the DKI Jakarta Provincial Government. The purpose of this study is to determine whether service has an effect on community satisfaction. The method used is descriptive quantitative with data analysis using simple linear regression analysis. Data collection was carried out by distributing questionnaires. From the research results it is known that there is an effect of service on community satisfaction by 35.3% in RPTRA in the Jakarta area during the Covid-19 pandemic. The results of this study indicate that there is a positive and significant effect of service on community satisfaction. Keywords: services, rtpra, community satisfaction, covid 19 pandemic, jakarta